Matematică
teodinu
2015-11-13 18:30:54
19*7*[3+2*(14*2-7,4)+2,1]+22,12
Răspunsuri la întrebare
CasTieL
2015-11-13 20:12:35

19×7×[3+2×(14×2-7,4)+2,1]+22,12 133×[3+2×(28-7,4)+2,1]+22,12= 133×[3+2×20,6+2,1)+22,12= 133×(3+41,2)+22,12= 133×44,2+22,12= 133×44,2+22,12= 5878,6+22,12=5900,72

andreeadeea8026
2015-11-13 20:13:50

19*7*[3+2*(14*2-7,4)+2,1]+22,12= =19*7*[3+2*(28-7,4)+2,1]+22,12 =19*7*(3+2*20,6+2,1)+22,12 =19*7*(3+41,2+2,1)+22,12 =19*7*46,3+22,12 =133*46,3+22,12 =6157,9+22,12 =6180,02

Adăugați un răspuns